Lipopolysaccharide Preparation Derived From Porphyromonas gingivalis Induces a Weaker Immuno-Inflammatory Response in BV-2 Microglial Cells Than Escherichia coli by Differentially Activating TLR2/4-Mediated NF-κB/STAT3 Signaling Pathways - Qiu, Che; Yuan, Zhen; He, Zhiyan; Chen, Huiwen; Liao, Yue; Li, Shiliang; Zhou, Wei; Song, Zhongchen (Frontiers in Cellular and Infection Microbiology, 2021)
Alzheimer's disease (AD) is a degenerative disease of the central nervous system with unclear etiology and pathogenesis. In recent years, as the infectious theory and endotoxin hypothesis of AD has gained substantial attention, several studies have proposed that Porphyromonas gingivalis (P. gingivalis), one of the main pathogenic bacteria of chronic periodontitis, and the lipopolysaccharide (LPS) of P. gingivalis may lead to AD-like pathological changes and cognition impairment. However, research on the relationship between P. gingivalis-LPS and neuroinflammation is still lacking. Our study aimed to investigate the effects of P. gingivalis-LPS preparation on immuno-inflammation in microglial cells, and further compared the differential inflammatory response induced by P. gingivalis-LPS and Escherichia coli (E. coli) LPS preparations. The results showed that P. gingivalis-LPS could upregulate the gene expression and release of pro-inflammatory factors in BV-2 microglial cells, including IL-1β, IL-6, TNF-α, IL-17, and IL-23. We also observed an increase in the level of Toll-like receptor 2/4 (TLR2/4) and NF-κB/STAT3 signaling. Moreover, the changes mentioned above were more significant in the E. coli-LPS group and the effects of both kinds of LPS could be differentially reversed by the administration of the TLR2 inhibitor C29 and TLR4 inhibitor TAK-242. The molecular simulation showed that the binding affinity of P. gingivalis-lipid A to TLR4-MD-2 was weaker than E. coli-lipid A, probably due to the fewer number of acyl chains and phosphate groups of P. gingivalis-lipid A than of E. coli-lipid A. We conclude that P. gingivalis-LPS could activate TLR2/4-mediated NF-κB/STAT3 signaling pathways, which ultimately resulted in immune-inflammatory response in BV-2 microglia. In contrast to E. coli-LPS, P. gingivalis-LPS is a weaker TLR2/4 agonist and NF-κB/STAT3 signaling activator. Furthermore, the different fatty acid chains and phosphate groups between P. gingivalis-lipid A and E. coli-lipid A may be the reason for the weaker activating properties of P. gingivalis-LPS.